2020
DOI: 10.1016/j.jacc.2020.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Diversity in Cardiology

Abstract: Corresponding Author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Initiatives to increase diversity in cardiology and radiology have been developed by the American College of Cardiology (ACC), American Heart Association (AHA), and ACR and should be intentionally promoted within the field of cardiovascular imaging. 13,28,29 To achieve diversity, equity, and inclusion in cardiovascular imaging, it is essential to focus on the training pathways for cardiology fellows, radiology residents and fellows, internal medicine residents, and medical students. 29,30 Unfortunately, a recent survey of cardiology fellowship program directors found that only 6% of cardiology fellowship program directors rank diversity as a top 3 priority when making their fellowship rank list.…”
Section: Workforce Shortages and Underrepresentation In Cardiac Imagingmentioning
confidence: 99%
“…Initiatives to increase diversity in cardiology and radiology have been developed by the American College of Cardiology (ACC), American Heart Association (AHA), and ACR and should be intentionally promoted within the field of cardiovascular imaging. 13,28,29 To achieve diversity, equity, and inclusion in cardiovascular imaging, it is essential to focus on the training pathways for cardiology fellows, radiology residents and fellows, internal medicine residents, and medical students. 29,30 Unfortunately, a recent survey of cardiology fellowship program directors found that only 6% of cardiology fellowship program directors rank diversity as a top 3 priority when making their fellowship rank list.…”
Section: Workforce Shortages and Underrepresentation In Cardiac Imagingmentioning
confidence: 99%
“…While the disconnect between career preferences and cardiology perceptions held true for both male and female residents, the continued difficulty in attracting women into cardiology fellowships is of particular concern . The survey was redeployed to explore current IM residents’ career aspiration preferences and perceptions of cardiology and possible changes over time, with the intention of better understanding the continued obstacles to recruiting women into cardiology …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The survey was redeployed to explore current IM residents' career aspiration preferences and perceptions of cardiology and possible changes over time, with the intention of better understanding the continued obstacles to recruiting women into cardiology. 6…”
mentioning
confidence: 99%
“…Increased diversity in medical fields has been shown to contribute to improved overall patient experience, clinical care decisions, and quality of patient care [ 4 - 5 ]. Despite the advantages of having a diverse physician workforce, the field of cardiology has failed to keep pace with the increasingly diverse patient population of the United States [ 6 ]. In fact, 30% of cardiovascular training programs accredited by the American College of Graduate Medical Education (ACGME) had no URMs, and over half had only between 1% and 25% of fellows that comprised that category [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, 30% of cardiovascular training programs accredited by the American College of Graduate Medical Education (ACGME) had no URMs, and over half had only between 1% and 25% of fellows that comprised that category [ 7 ]. Underrepresentation has not gone unnoticed by the broader physician community, as evidenced by the 2019 establishment of workforce diversity guidelines by the ACGME, which have been described as a “wake-up call” to cardiology [ 6 ]. Moreover, the 2020 retraction of an article published by a cardiology fellowship program director due to numerous misconceptions, inaccuracies, and other invalidities regarding diversity underscores the necessity of continued research in this subject [ 8 ].…”
Section: Introductionmentioning
confidence: 99%